High-Quality Genome Assembly and Annotation Resource of Elsinoë annonae, Causing Fruit Scab on Camellia oleifera - Bao, Jiandong (Plant disease, 2023)
Elsinoë annonae is a fungal pathogen that causes fruit scab disease in the edible-oil (tea oil) plant (Camellia oleifera Abel). The absence of genome resources for this fungus hampers functional genetic studies of the pathogenesis mechanism of E. annonae. This study reports the genome assembly of E. annonae strain SM-YC-2 collected from tea oil tree fruit with scab disease in Fujian Province, China. Combining 16.44 Gb of PacBio Sequel II long reads and 5.13 Gb of Illumina NovaSeq reads, we generated a 25.93-Mb (99.19% of expected genome size) high-quality genome assembly with 52.66% GC content, 5.05% repeats, and over 98% Benchmarking Universal Single-Copy Orthologs completeness for E. annonae strain SM-YC-2. These high-quality genome assembly resources will facilitate functional genomic characterization studies, enhance insights into the pathogenicity mechanism of E. annonae, and support the development of molecular-based control strategies